The development and clinical use of the Guy's and St Thomas' quality of life questionnaire (GAST) for adult cochlear implant patients. (2nd January 2022) - Driver, Sandra; Soulby, Andrew; Shallita, Natasha; Walters, Hazel; Jones, Isabelle; Jiang, Dan
Abstract : Objectives: To Review the benefit of the GAST questionnaire (Tilston, S. 2003. Assessing the quality of life in adult cochlear implant users. MSc dissertation. London: City University.) to measure hearing related quality of life for adults pre and post-cochlear implantation. To develop a scoring methodology as to what score constitutes a significantly 'good' or 'poor' change to better target rehabilitation to those most in need. Design: The GAST Questionnaire was developed using a robust cycle of validation and reliability analyses using the Statistical Package for the Social Sciences (Norusis, M. 1993. SPSS for windows: professional statistics. release 6.0 . Chicago: SPSS Inc.). The scoring methodology was developed by dividing 83 patient full data sets into quintiles for the delta of quality of life improvement and the 9–12 month post-implantation GAST score. Results: The GAST questionnaire design was deemed robust. The scoring methodology used led to the 20th percentile score highlighting individuals requiring further support and the 80th percentiles for those suitable for partial booking. Conclusion: The GAST questionnaire is a useful way of identifying the patients in need of support as well as to measure patient reported quality of life improvements following cochlear implantation.